Hepatitis delta virus (HDV): Some Details and features - Yasir , Saif Jabbar; Al- Makhzoomy, Taghreed Abdul kareem (Medical Science Journal for Advance Research, 2021)
The hepatitis D virus causes liver disease. It affects all ages. Some call it "delta hepatitis" (HDV). Hepatitis D patients have previously had hepatitis B, which is why they have this illness. Hepatitis D is spread when contaminated blood or bodily fluids come into contact with an uninfected person's body. Hepatitis D can be an acute infection or a chronic illness, depending on the person. Hepatitis D can produce severe symptoms, liver damage that lasts a lifetime, and even death. Hepatitis B and D viruses can infect people at the same time (coinfection) or they might develop hepatitis D after getting hepatitis B (reverse coinfection) (a condition known as "superinfection"). Hepatitis D is not prevented by immunisation. Hepatitis B vaccination, on the other hand, protects against hepatitis D infection.